The Relevance and Challenges of an Economic Evaluation of Florida's 4-H Program - Alfonso Flores-Lagunes; Troy Timko (EDIS)
FE753, a 4-page fact sheet by Alfonso Flores-Lagunes and Troy Timko, describes the 4-H program and the importance of economic evaluation of its impact, provides a primer on economic evaluation of programs, and lays out a research roadmap for accumulating the data necessary for an economic evaluation of the Florida 4-H program. Includes references. Published by the UF Department of Food and Resource Economics, October 2008.